The Italian Mezzogiorno: markets or policies? - BOLTHO, A. (PSL Quarterly Review, 2013)
Two authoritative institutions, the Italian Treasury and the OECD, have recently joined the debate on how best to promote the development of Southern Italy. While the former argued for a multi-faceted strategy emphasising the importance of increasing capital, the latter maintained that governments should refrain from policy activism and instead limit public intervention to infrastructure and public goods. The issue at stake, however, is not the crude one of whether development is best promoted by laissez faire or by intervention, but the much subtler one of the right proportions in which policies and market forces should be combined. The purpose of this brief note is to look at which of the two approaches is, in the light of past evidence, the one most likely to further Southern development. JEL: O20, O52